Contribution of continuing education about hand hygiene in the fight against COVID-19: an experience report - Lima, Aline Magalhães de; Silva, Daniel Pereira da; Araújo, Handeson Brito; Sampaio, Luana Thamires da Costa; Lima, Telma Vieira; Batista, Odinéa Maria Amorim (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: Amid COVID-19 pandemic, the use of protective measures, as hand hygiene, is necessary due the easiness of transmission through contact. Aim: To report the developed activities about hand hygiene, before the pandemic, in a university extension program which can contribute to reduce COVID-19 transmission within health service. Outlining: Descriptive study with qualitative approach, experience report type, of the activities carried out in the extension project “Surveillance of Risk Factors and Protection for Healthcare Related Infection by the Search and Notification of Cases”, the year of 2019. Results: The developed activities ranged from the monitoring of the practice of hand hand hygiene until the development of educational activities which aim the adhesion by the professionals, being an important practice for controlling infections that can be transmitted through the hands. Implications: The increase of hand hygiene adhesion, through educational activities, can contribute to the reduction of COVID-19 transmission risk within the hospital services.